A heterostructure membrane with natural-light photocatalytic activity. (September 2020) - Zhang, Weiye; Wen, Yuling; Wu, Mengjie; Zhang, Jia; Qian, Guangren
Graphical abstract: Abstract: For the first time, a heterostructure was synthesized by bismuth oxychloride and Zn-Cr layered double hydroxide. A novel membrane photocatalyst was then obtained by dispersing the heterostructure in polyvinylidene fluoride. Under visible light, the membrane removed 99.9% of Rhodamine B after 240 min. Under sun light, the removal even reached over 80% after 360 min. The heterostructure effectively inhibited the recombination of electron–hole pairs and promoted the production of active species, thus improving the natural-light activity. The degradation mechanism for Rhodamine B was attributed to photocatalysis and photosensitization. Moreover, the formation of membrane improved the reusage of photocatalyst. Therefore, this work put forward a potential natural-light photocatalyst for a real application.